TURKISH WRITING IS A PRECIOUS HERITAGE OF KAZAKH HISTORY - Nurkeldi Zharasbaev (Galaxy International Interdisciplinary Research Journal, 2022)
As you know, our modern history has entered the stage of history as a separate nation, which became a kind of Homeland in the era of the formation of the Turkic-speaking peoples after the Middle Turkic period.